A Study On Meditation Practices On Self Esteem Among Middle Aged Working Women (Journal of Pharmaceutical Negative Results, 2023)
Introduction: The purpose of the present study was to investigate the effect meditation practices on self esteem among middle aged working women.Aim and Objective: To achieve the purpose of the study thirty working women were selected from Karaikudi (Urban), Tamilnadu, India during the year 2022.Materials and methods: The subject’s age ranges from 35 to 45 years. The selected women subjects were divided into two equal groups consists of 15 subjects each namely experimental group and control group. The experimental group underwent a meditation practices programme for ten weeks. The control group was not taking part in any training during the course of the study. Self esteem was taken as criterion variable in this study. The selected subjects were tested on self esteem was measured through Rosenberg Self-Esteem Scale (RSE) (psychological questionnaire). Pre-test was taken before the training period and post- test was measured immediately after the ten week training period. Statistical technique‘t’ ratio was used to analyse the means of the pre-test and post test data of experimental group and control group.Results: The results revealed that there was a significant difference found on the criterion variable.Conclusion: The difference is found due to meditation practices given to the experimental group on self esteem when compared to control group.